Pengaruh Diversifikasi Usaha Dan Pengendalian Internal Terhadap Penghindaran Pajak (Studi Empiris Pada Perusahaan Tambang Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Stefani Febriani; Khairudin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This research was conducted to demonstrate the impact of business diversification and internal control on tax avoidance empirically. The independent variables tested are business diversification and internal control. The data in this study uses secondary data from the financial reports of companies listed on the IDX for 2019-2021. The sample was selected using the purposive sampling method in order to obtain a sample of up to 10 companies. The data analysis used is panel data regression analysis. The results of the study show that in the case of tax avoidance, business diversification doesn’t have a significant effect, while internal control has a negative effect.